The presumption of innocence: A golden thread always to be seen - CHIA, Mark Zi Han (Institutional Knowledge at Singapore Management University, 2021)
Although the presumption of innocence is fundamental to the modern criminal justice system, there is little clarity on what it is and how it applies. This essay argues that “innocence” in the criminal justice system should be confined to legal innocence and not factual innocence. Accordingly, the presumption of innocence should be confined to presuming the legal innocence of an accused. It follows then that the presumption of innocence cannot apply to any part of the criminal process apart from the trial itself. Further, jurisprudentially, given that the presumption of innocence is best understood as a procedural aspect of the right to a fair trial, the existing law needs to be reformed in some aspects so as to accommodate such a conception of the presumption. To that end, this essay proposes some possible reforms as a way to move forward.